(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Emotional intelligence and personality traits are associated with personal satisfaction experienced by the subjects, according to certain studies. In turn, the relationship between personality factors, emotional intelligence and teacher self-sufficiently is also important. A study on emotional intelligence was carried out with 160 students from the Faculty of Education at the University of Zaragoza, specialising in the areas of physical education, primary education, foreign language and special education, measuring levels of emotional intelligence and personality traits. The results demonstrated how students with specialities that require a more vocational profile differ from other students who are studying other specialties. This thesis aims at investigating the impact of emotional intelligence on teacher’s job performance in the education sector of Pakistan. Sample size consists of 166 teachers from universities in the area of central Punjab, Pakistan. Theories of emotional intelligence proposed by Salovey and Mayer (1989–1990) were used as the conceptual framework and its relationship with the job performance of teachers was examined. Reliability and validity of variables was tested through measurement model of PLS-SEM. The result indicated that emotional intelligence has a significant impact on the teacher’s job performance. Key research finding revealed that emotional self-awareness, self-confidence, achievement, developing others and conflict management have a positive and significant relationship with the teacher’s job performance.